Influência da preparação do licor de jabuticaba (Myrciaria jaboticaba Vell berg) no teor de compostos fenólicos - Andrea Carrara Goecze (2007)
Epidemologist researches suggest that an association with the consumption of foods and drinks with a great concentration of phenolic compounds and the prevention of some diseases is possible. The medicinal aspect of these compounds is due to their antioxidant substances. The jabuticaba ( Myrciaria jaboticaba Vell berg) a nativeBrazilian fruit has a great concentration of phenolic compounds in its peel. The liqueur elaboration makes possible the extraction of phenolic compounds from all parts of the fruit. The preparation processes were defined according to three different ways of extracting soluble compounds from the fruits. The liqueur A was prepared by simple alcoholic aceration while in the liqueur B before the maceration the fruits were submitted to a 60º C thermal treatment during ten minutes. After the maceration a sucrose syrup was added. In the liqueur C preparation an osmotic dehydration was used, the syrup was done by the sugar and the alcoholic maceration occurred. In all the liqueurs the level of total soluble solids was adjusted to 30º Brix and the alcoholic level to 18% v/v. The phenolic levels ranged from 0,52 to 1,20 g/L, in this case the liqueur A appeared with the lowest level. The tannis level ranged from 0,47 to 0,75 g/ and theliqueur B showed the low level. There was a significant difference on the tannis level in each liqueur (A, B and C). The polymeric anthocyanins percentage ranged from 80,7 to 89,2%, the liqueur B showed the highest level. The TEAC (Trolox Equivalent Antioxidant Capacity) levels ranged from 1,88 to 2,88 in an interval of 2 minutes and from 2,48 to 3,61 mmol/L in an interval of 15 minutes. The liqueur C showed the biggestantioxidant power. The correlation among total phenolic, tannis and the antioxidant activity was considered positive and significant to the ABTS method in the 2 and 15 minute intervals of analysis. The liqueurs were submitted to an acceptance test and they had an acceptability indicator superior to 80% in all the evaluated aspects.